BOREAL-TETHYAN MOLLUSK MIGRATIONS AT THE JURASSIC-CRETACEOUS BOUNDARY TIME AND BIOGEOGRAPHIC ECOTONE POSITION IN THE NORTHERN HEMISPHERE - Zakharov V.A.; Rogov M.A. (My University, 2003)
Mollusk migrations of various intensity in the Kimmeridgian to Valanginian time span were established in the Boreal Atlantic (West and East European Provinces), Boreal Pacific (Chukotka-Canadian and Boreal Pacific Provinces), and Arctic Realms of the Panboreal Superrealm. According to intensity degree, the migrations are classified as expansions, i.e., mass migrations, and influence migrations, i.e., penetration of separate taxa. Migrations of the cross- and unidirectional types are distinguished according to directions of taxa exchange. Mollusks (ammonites, belemnites, and bivalves) are subdivided into Tethyan and Boreal forms, which inhabited areas south of 45°N, and north of 50°N, respectively. Low-boreal mollusks distinguished among the latter were characteristic of an ecotone between the Panboreal and Tethys-Panthalassa Superrealms, and Boreal-Arctic taxa dwelt north of 60°N. The ecotone of the Boreal Atlantic Realm was situated between 50° and 55°N. The ecotone zone persistently existed in the Boreal Pacific Realm. The ammonite ecotone of the Chukotka-Canadian Province (Primor'e) was between 45° and 55°N. In the Boreal Pacific Province (northern California), an ecotone of the Tithonian-Valanginian time was located between 40° and 50°N. Water temperature lower in the north was the major factor that influenced Boreal-Tethyan migrations and positioning of biogeographic ecotones. The coincidence of transgression peaks with the ammonite migration events is characteristic only of the Kimmeridgian-Middle Volgian time, when northward migrations of the Tethyan ammonites coincided with sea level rises. The Berriasian expansion of berriasellids to the Central Russian Sea was not associated with eustatic events. It might be a consequence of a sea way opening between the North Caucasian and Central Russian seas.
Keywords: Cretaceous; Jurassic; Boreal; Tethys; ecotone; biogeography; migrations; mollusks; Mesozoic::Cretaceous; Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Меловая